Antimicrobial Resistance Profile of E. coli Isolated from Raw Cow Milk and Fresh Fruit Juice in Mekelle, Tigray, Ethiopia - Haftay Abraha Tadesse; Netsenet Berhe Gidey; Kidane Workelule; Hagos Hailu; Seyfe Gidey; Abrha Bsrat; Habtamu Taddele (Veterinary Medicine International)
Aim. Foodborne illnesses represent a public health problem in developed and developing countries. They cause great suffering and are transmitted directly or indirectly between animals and humans and circulate in the global environment. E. coli are among them, causing a major public health problem. The aim of this study was therefore to study the antimicrobial resistance profile of E. coli from raw cow milk and fruit juice. Materials and Methods. A cross-sectional study was conducted from October 2016 to June 2017 on 258 samples collected from milk shops (n=86), dairy farms (n=86), and fruit juice (n=86) in different subcities of Mekelle. Bacteriological procedures were used for isolation of E. coli in the collected samples and for identification of the antimicrobial resistance profile. Result. The overall mean viable bacterial count and standard deviation of samples from milk shop, fruit juice, and dairy milk were found to be 8.86 ± 107, 7.2 ± 107, and 8.65 ± 107 CFU/ml and 33.87 ± 106, 6.68 ± 106, and 22.0 ± 106, respectively. Of the samples tested, 39 from milk shops (45.35%), 20 from fruit juice (23.26%), and 24 from dairy farms (27.91%) were found to be positive for E. coli. The isolated E. coli were highly resistant to ampicillin (70%), sulfamethoxazole-trimethoprim (60%), clindamycin (80%), erythromycin (60%), chloramphenicol (50%), and kanamycin (50%) and were found to be susceptible to some antibiotics like gentamicin (100%), norfloxacin (100%), tetracycline (60%), polymyxin B (90%), and ciprofloxacin (90%). Conclusion. The current study supports the finding that raw milk and fruit juice can be regarded as critical source of pathogenic E. coli. This supports the need for strict monitoring and the implementation of effective hygienic and biosecurity measures in the whole food chain of these products as well as a prudent use of antimicrobials.